2009
DOI: 10.1002/zaac.200900199
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Crystal Structures of InGaO3(ZnO)m (m = 2 and 3)  

Abstract: , respectively, was confirmed by valence sum calculations. The structure of InGaO 3 (ZnO) 3 was refined from powder X-ray diffraction data. InGaO 3 (ZnO) 3 crystallises trigonal (R 3;¯m; No. 166; a = 3.2871(9) Å; c = 41.589(1) Å, R Bragg = 0.0506). The space group was confirmed by CBED. The structure of InGaO 3 (ZnO) 3 is similar to InGaO 3 (ZnO) 2 , however, the wurtzite type part of the structure has an even number of closed packed oxygen layers and thus the inversion boundary within this area is different. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 23 publications
(31 reference statements)
2
35
0
1
Order By: Relevance
“…Therefore, it seems from these observations that we have not been successful in the synthesis of the homologous compound m = 8. This result is consistent with previous studies that showed that samples with even values of m are more difficult to synthesize that samples with odd values of m, and with the fact that the successful synthesis of InGaO 3 (ZnO) 8 has never been reported in the literature. Contrary to this situation, no inhomogeneity of the concentration of In has been observed for m = 6 and 7 (representative examples of In elemental mappings at various scales are shown in Figure S15).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, it seems from these observations that we have not been successful in the synthesis of the homologous compound m = 8. This result is consistent with previous studies that showed that samples with even values of m are more difficult to synthesize that samples with odd values of m, and with the fact that the successful synthesis of InGaO 3 (ZnO) 8 has never been reported in the literature. Contrary to this situation, no inhomogeneity of the concentration of In has been observed for m = 6 and 7 (representative examples of In elemental mappings at various scales are shown in Figure S15).…”
Section: Resultssupporting
confidence: 93%
“…[1][2][3][4] In this structure, octahedral-coordinated In atoms form an [InO 2 ] − layer, whereas Zn and Ga atoms occupy distorted tetrahedra and bipyramids and form a [GaZn m O m+1 ] + layer, with a distribution of Zn and Ga that is still under debate and may depend on the value of m (see for example Ref. [5][6][7][8]). To date, outside their crystallographic properties, they have been mostly studied in the thin film form.…”
Section: Introductionmentioning
confidence: 99%
“…The result shows that InGaO 3 (ZnO) 4 is a member of the structure family with general formula ARO 3 (ZnO) m . The compound has the same type of structure like InGaO 3 (ZnO) 2 , which was solved earlier 10. The structure may be regarded in terms of closed‐packed oxygen ions.…”
Section: Resultsmentioning
confidence: 93%
“…The displacement parameters of O4, the oxygen ion in the equatorial plane of the GaO 5 unit, are elongated along c . A comparison between the components with m = 2 10 and m = 4 shows an increasing displacement parameter of O4, which may indicate a split position. Attemps to refine a split position for this oxygen atom showed no reasonable results.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation